The Ethical Perils of Representing the Juvenile Defendant Who May Be Incompetent - Lynda E. Frost; Adrienne E. Volenik (Washington University Journal of Law & Policy, 2004)
With the evolution of juvenile court to a more punitive criminalized model, the issue of adjudicative competence has taken on a newfound importance. Potentially impaired juveniles present attorneys with complicated situations that have three dueling interests: the client’s wishes, the best interests of the child, and the attorney’s obligations as an officer of the court. This Essay examines questions likely to arise with respect to these interests when an attorney suspects his or her juvenile client may be incompetent. Part I reviews the doctrine of adjudicative competence in the context of adult criminal proceedings. Part II summarizes the newly evolved application of the doctrine in juvenile court. Part III examines the ethical, legal, and practical considerations that arise when a lawyer has concerns about whether a juvenile client possesses the competence needed to participate appropriately in juvenile court proceedings.
Keywords: Legal ethics; Juvenile delinquents; People with mental disabilities